Desorption properties of mechanically milled MgH2 with double catalysts Ni and SiC. Issue 1 (September 2020) - Rahwanto, A; Jalil, Z; Akhyar; Handoko, E
Abstract: The study of the MgH2 double-catalyzed Ni and SiC based storage system has been done. The objective of this study is to improve the hydrogen desorption temperature and the hydrogen desorption capacity. The material preparation was done through mechanical alloying technique. In this method, the milling of the material was carried out within 5 hours, 10 hours and 15 hours, with the ratio of the ball to the powder was and the speed of 350 rpm with the catalyst insertion catalyst by 5 wt% and 10 wt% SiC. Results from XRD measurements revealed that the sample was successfully reduced to a nanocrystal scale. The phase emerging from the XRD observation is the phase MgH2 as the main phase and followed by Ni and SiC phase as the minor phase. From the observation with SEM showing irregular particle shape, the particle size in the sample is not homogeneous because of the agglomeration effect and cold welding that causes the particle size to look large. The hydrogen release capacity was obtained in the samples which were milled for 10 hours at the weight of 5 wt% Ni-SiC catalyst with the release of 2.6 wt%. Based on observation with thermogravimetric analyzer (TGA), the lowest temperature was obtained in the samples which were milled 10 hours with catalyst 5 wt% SiC, which was 365 °C.